Imperfections and Shortcomings of the Stakeholder Model’s Graphical Representation - Fassin, Yves (Journal of business ethics, 2008)
The success of the stakeholder theory in management literature as well as in current business practices is largely due to the inherent simplicity of the stakeholder model––and to the clarity of Freeman’s powerful synthesised visual conceptualisation. However, over the years, critics have attacked the vagueness and ambiguity of stakeholder theory. In this article, rather than building on the discussion from a theoretical point of view, a radically different and innovative approach is chosen: the graphical framework is used as the central perspective. The major shortcomings of the popular stakeholder framework are systematically confronted with the graphical scheme to illustrate their visual impact. The graphical illustrations of the imperfections help explain the sometimes-oversimplified generalisation inherent to every graphical model. They also make some interrelationships easier to understand. The analysis demonstrates that, with the tacit but implicit acceptance of simplification of the discussed explanatory elements, Freeman’s framework remains a rather good approximation of reality. Only a few minor changes to the stakeholder model are consequently proposed.